The Role of Macrophages in Cardiac Function and Disease - Nella Prevete; Daniela Sorriento (MDPI AG, 2023)
A tight association between inflammation and cardiac damage has been extensively recognized. In this review, we will focus on macrophages as key players in the physiology and pathology of the heart and on their role in the functional crosstalk between inflammation and heart disease. In the steady state, macrophages contribute to the homeostasis of cardiac tissue. Indeed, cardiac resident macrophages promote coronary development and tissue homeostasis, favor electric conduction in cardiomyocytes, and contribute to mitochondrial quality control. However, macrophages also take part in adverse cardiac events contributing to the development or the progression of several pathologic conditions. Infiltrating cells derived from circulating monocytes contribute to tissue injury through the release of inflammatory cytokines and catecholamines. In particular, the present review will discuss the role of macrophages in heart failure, atherosclerosis, and anthracycline-dependent cardiotoxicity. Prolonged inflammatory response and increased apoptotic cell death sustained by chronic activation of the transcription factor NFκB are the basis of heart failure pathogenesis. Here, we will discuss the involvement of NFκB signaling in macrophage-dependent cardiac damage and its use as a therapeutic target in the treatment of cardiovascular pathologies.